The effects of political communication on young voters political information efficacy and sense-making process: a case study in Dun Kota Damansara (Selangor) / Suhaimee Saahar @ Saabar - Saahar @ Saabar, Suhaimee (2018)
In election, young voters will be exposed with variety of political information. One of the main political information sources during election campaign is through political advertising. Political advertisements that created during election campaigns serve multi purposes, either to persuade, influence, attacking, informing and manipulate the voters' information seeking and voting behaviour. In this study, mixed method was used to study the effect of political communication on young voters' political information efficacy and sense-making process in DUN Kota Damansara, Selangor. Firstly, focus group discussion through Sense-Making Methodology based on theory developed by Dervin was conducted to analyses how young voters' political situation affect their information needs and usage. Survey was used as the second method and its role as developing a structural model to confirm and develop a new theoretical framework that can later name as Political Ads Sense Efficacy to measure the effect of political advertising on young voters' behaviour. The findings show that young voters in this study choose political parties as their main factor of selection rather than candidates. At the same time, they believed that manifesto just political promises by political parties in winning an election. Therefore, this thesis discussed the role of political advertising in voters' information seeking and voting behaviour. Political advertising has a great impact on young voters' political ads sense efficacy in terms of their understanding and experience in influencing their political decision. Therefore, this thesis has proven that political advertising, political information efficacy and sense-making can be strong predictors to predict the outcome of election.